2016
DOI: 10.1080/15592324.2016.1155017
|View full text |Cite
|
Sign up to set email alerts
|

On growth and formins

Abstract: Development of the plant aerial organs epidermis involves a complex interplay of cytoskeletal rearrangements, membrane trafficking-dependent cell surface expansion, and intra-and intercellular signaling, resulting in a pattern of perfectly interlocking pavement cells. While recent detailed in vivo observations convincingly identify microtubules rather than actin as key players at the early stages of development of pavement cell lobes in Arabidopsis, mutations affecting the actin-nucleating ARP2/3 complex are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Unless the effects of the fh1 mutation differ between trichomes and pavement cells, a possible explanation of the apparent paradox is that increased microtubule mobility in fh1 mutants may promote generation of transient microtubular structures required for branch initiation, while microtubule stabilization increases the lifetime of such structures. This would be consistent with our hypothesis explaining increased pavement cell lobing in fh1 mutants by enhanced generation of microtubule bundles at future pavement cell lobe necks (Cvrčková et al, 2016). Additional observations, focusing on cytoskeletal dynamics during early stages of trichome ontogeny, are needed to test this hypothesis.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Unless the effects of the fh1 mutation differ between trichomes and pavement cells, a possible explanation of the apparent paradox is that increased microtubule mobility in fh1 mutants may promote generation of transient microtubular structures required for branch initiation, while microtubule stabilization increases the lifetime of such structures. This would be consistent with our hypothesis explaining increased pavement cell lobing in fh1 mutants by enhanced generation of microtubule bundles at future pavement cell lobe necks (Cvrčková et al, 2016). Additional observations, focusing on cytoskeletal dynamics during early stages of trichome ontogeny, are needed to test this hypothesis.…”
Section: Discussionsupporting
confidence: 84%
“…Arabidopsis mutants with impaired actin nucleation commonly exhibit altered pavement cell shape and size (e.g. Li et al, 2003;Mathur et al, 2003a;Mathur et al, 2003b;El-Assal et al, 2004;Basu et al, 2004;Basu et al, 2005;Rosero et al, 2016;Sahi et al, 2018;Oulehlová et al, 2019), again consistent with microfilaments contributing to early microtubule rearrangements that establishes the lobe layout (compare Cvrčková et al, 2016), albeit cytoskeletal organization and dynamics during early pavement cell development in these mutants remains to be characterized.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Using static image analysis and manual tracking of filaments labeled with several different marker proteins, we have previously shown that fh1 mutants exhibit increased microfilament bundling and thus increased actin structure lifetime both in rhizodermis and in cotyledon pavement cells [25, 26], possibly as a consequence of weakening the trans-plasmalemma attachment of cortical microfilaments to the cell wall [48] that may allow for easier lateral movement and thus bundling of individual microfilaments [49]. QuACK analyses convincingly confirmed increased lifetime of actin structures in fh1 mutants.…”
Section: Discussionmentioning
confidence: 99%
“…LOC100273612 and At4g29310 were annotated as formin-like protein 18 ( Figure 2D). Formin is an essential regulator of cytoskeleton and directly controls cell division and expansion (Cao et al, 2016;Cvrckova et al, 2016;Rosero et al, 2016). However, DUF1005 did not possess the basic FH2 (Formin Homology 2) domain of forminlike protein (Dominguez, 2009).…”
Section: Vrse1 Is a Duf1005 Domain-containing Protein And May Regulatmentioning
confidence: 99%